Government Wage Bill Management and Civil Service Reform in the Eastern Caribbean Currency Union - Mitchell, A. E. Wayne (IMF Working Papers; Working Paper, 2019)
In this study, we assess the size of the government wage bill and employment in the member countries of the Eastern Caribbean Currency Union and their implications for fiscal sustainability and the adequacy of public service delivery. Over the period 2005 to 2015 their wage bill (as a percentage of GDP, government revenues and expenditures) is higher than in other small states notwithstanding recent efforts by governments to make it more manageable. The composition and distribution of employment is sub-optimal and is reflected in skills mismatches contributing to inefficiencies in public service delivery. Using a dynamic fixed-effects panel, we find that wage bill growth reflects the expansion of government activities to speed up economic and social development and that wage bill spending is procyclical in good times but is rigid during downturns. Finally, we identify the main institutional and legal reforms needed to improve wage bill management and public service efficiency.